An Affective Domain Evaluation in Islamic Education: A Perspective from Self-Determination Theory - Maulidya Nisa; Siti Salma Shobihah; Mokh Iman Firmansyah; Agus Fakhruddin; Saepul Anwar (Universitas Muhammadiyah Malang, 2024)
This research aims to analyze various problems of the evaluation system in the affective domain of Islamic Education. In addition, this research based on Deci and Ryan's Self-Determination Theory. This research is important to do because of the urgency related to the various problems in evaluation system, especially in affective domain related to Islamic education in Indonesia. This research used a qualitative approach and library research to obtain data related to the reality of the evaluation system in affective domain with Deci & Ryan's Self-Determination as a theory. Researchers searched the references from various books and articles through Google Scholar. The research showed that an evaluation system in the affective domain based on Self-Determination theory will give more possibility to teacher for emphasize the fulfilment of three basic human psychological needs such as autonomy, competence, and relatedness. This principle can be applied by measuring student's basic needs and examining how these needs can be fulfilled through the education provided. This research has implications in improving the quality of evaluation system in Indonesia, especially in the affective domain. However, this research only focuses on measuring the affective domain in Islamic Education, so further research must be done. This research focus on the evaluation system of the affective domain in Islamic Education by providing a new point of view with Self-Determination Theory (SDT) as a reference.